2021
DOI: 10.1021/acs.jmedchem.1c00794
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multivalent Sialylated Polyglycerols for Resistance Induction in and Broad Antiviral Activity against Influenza A Viruses

Abstract: The development of multivalent sialic acid-based inhibitors active against a variety of influenza A virus (IAV) strains has been hampered by high genetic and structural variability of the targeted viral hemagglutinin (HA). Here, we addressed this challenge by employing sialylated polyglycerols (PGs). Efficacy of prototypic PGs was restricted to a narrow spectrum of IAV strains. To understand this restriction, we selected IAV mutants resistant to a prototypic multivalent sialylated PG by serial passaging. Resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 103 publications
0
22
0
Order By: Relevance
“…Furthermore, Stadtmueller et al discovered that structural mutation in HA reduced stable binding of 6′-sialyllactose (SL) with HA. 83 It has been demonstrated that drugs–nanoparticle conjugates exhibit significantly enhanced antagonist effects. Bu et al assessed the binding kinetics of the anti-PD-L1 (aPD-L1) antibody-conjugated multivalent dendrimers ( n = 3.7) with PD-L1, 84 revealing that dendrimer–aPD-L1 conjugates significantly enhanced binding avidity to PD-L1 compared with aPD-L1 ( k off = 6.00 × 10 −1 s −1 ).…”
Section: Drug Discovery and Verification Using Afmmentioning
confidence: 99%
“…Furthermore, Stadtmueller et al discovered that structural mutation in HA reduced stable binding of 6′-sialyllactose (SL) with HA. 83 It has been demonstrated that drugs–nanoparticle conjugates exhibit significantly enhanced antagonist effects. Bu et al assessed the binding kinetics of the anti-PD-L1 (aPD-L1) antibody-conjugated multivalent dendrimers ( n = 3.7) with PD-L1, 84 revealing that dendrimer–aPD-L1 conjugates significantly enhanced binding avidity to PD-L1 compared with aPD-L1 ( k off = 6.00 × 10 −1 s −1 ).…”
Section: Drug Discovery and Verification Using Afmmentioning
confidence: 99%
“…These can be categorized as (1) polymers with different functional groups, (2) polymers that mimic AMP and (3) peptide-polysaccharides, which are combinations of peptides and polysaccharides. A wide variety of polymers bearing positive and negative charges, like biguanide polymers, 35 quaternary ammonium polymers, 36 phosphonium polymers, N-halamine polymers, 37 sulfated polymers, 38 sialylated polymers, 39 and phosphonothioate polymers can be prepared by introducing the respective functionalities to the polymer backbone. Polymeric AMP mimics such as poly( phenylene ethnylene)-based conjugated polymers with amino side groups show excellent antimicrobial properties and also low toxicity because of their amphipathic structural arrangement.…”
Section: Reviewmentioning
confidence: 99%
“…[52,53] Since each monomer of the HA 3 has a receptor binding site (RBS) for SA, therefore, scaffolds decorated with SA moieties thus competing with cell surface virus receptors have been favorably implemented in several studies to inhibit the activity of HA and thus influenza virus replication. [54][55][56][57][58][59] Considering the trimeric spatial organization of HA, a high affinity tripodal/ trivalent ligand could be designed by choosing an appropriate trivalent core and a spacer to bring the three HA-binding moieties in the right geometry that matches the RBSs of HA 3 . Several research studies have demonstrated the significance of 1,3,5-trisubstituted benzene scaffold for C 3 symmetric presentation of glycosidic ligands to construct trivalent/tripodal glycosides for lectin binding and other biological applications.…”
Section: Hemagglutininmentioning
confidence: 99%
“…Since each monomer of the HA 3 has a receptor binding site (RBS) for SA, therefore, scaffolds decorated with SA moieties thus competing with cell surface virus receptors have been favorably implemented in several studies to inhibit the activity of HA and thus influenza virus replication [54–59] . Considering the trimeric spatial organization of HA, a high affinity tripodal/trivalent ligand could be designed by choosing an appropriate trivalent core and a spacer to bring the three HA‐binding moieties in the right geometry that matches the RBSs of HA 3 .…”
Section: Hemagglutininmentioning
confidence: 99%